Evidence of Validity and Factorial Invariance of a Brief Jealousy Scale in Peruvian University Students - Ventura León, José (2018)
The study sought to analyze the evidences of validity, factorial invariance and reliability of the scores of the Jealousy Subscale of the Inventory of Emotional Communication in Romantic Relationships (Sanchez, 2012). To that effect, there was a sample of 1176 Peruvian university students who completed the 11 items of the original version. The confirmatory factor analysis verified a satisfactory adjustment of a final model of nine items in a single factor and correlated errors. It is concluded that the Jealousy scale is a measure that can be used in the professional and research activity, obtaining valid interpretations, reliable and invariant scores according to gender in Peruvian university students.